2022 International Power Electronics Conference (IPEC-Himeji 2022- ECCE Asia) 2022
DOI: 10.23919/ipec-himeji2022-ecce53331.2022.9806868
|View full text |Cite
|
Sign up to set email alerts
|

EMC Implications of Implementing WBG Devices in Battery Charger Modules for Electric Vehicles

Abstract: GaN and SiC semiconductor devices have the potential of drastic downsizing of power converters in applications where size is strictly limited like in electromobility. In electric powertrains, on-board chargers need to operate in a wide voltage and power range limited by the battery and its conditions. In this context, both size and voltage-power range can be achieved through the effective utilization of GaN and SiC devices. Nevertheless, although GaN and SiC devices offer outstanding features in fast transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Once again, electromagnetic compatibility issues due to the use of GaN devices in OBCs must be also carefully considered. In fact, the good features of GaN in terms of low on-resistance and fast switching are paid in terms of higher emissions that could ask for additional circuitry to mitigate them, which can jeopardize the high-power density target [39].…”
Section: Introductionmentioning
confidence: 99%
“…Once again, electromagnetic compatibility issues due to the use of GaN devices in OBCs must be also carefully considered. In fact, the good features of GaN in terms of low on-resistance and fast switching are paid in terms of higher emissions that could ask for additional circuitry to mitigate them, which can jeopardize the high-power density target [39].…”
Section: Introductionmentioning
confidence: 99%
“…To protect users from these risks, most charging devices use a communication and control line in addition to the power line to monitor the charging status in real time [14,15]. Despite these efforts, there have been reported instances of the intermittent termination of communication sequences and occasional errors in these charging systems [16][17][18][19][20][21][22]. While the exact causes of these phenomena are likely diverse, the authors have identified electromagnetic interference (EMI) as a significant contributing factor, arguing that a thorough analysis of the degradation of communication performance due to EMI coupling is necessary.…”
Section: Introductionmentioning
confidence: 99%